Bismuth metal–organic frameworks derived bismuth selenide nanosheets/nitrogen–doped carbon hybrids as anodes for Li–ion batteries with improved cyclic performance. Issue 9 (15th June 2019) - Li, Zhongchun; Pan, Honglin; Wei, Wenxian; Dong, Anliang; Zhang, Kailong; Lv, Hongying; He, Xianghong
Abstract: Nanohybrids have significant potential in improving the performance of Li–ion batteries (LIBs). Herein, bismuth selenide nanosheets/nitrogen–doped carbon hybrids (Bi2 Se3 @NC) are prepared by selenylation of bismuth (III) metal–organic frameworks (Bi–MOFs), which are obtained by solvothermal reaction in a mixed solvent of N, N–dimethylformamide and methanol. When served as anodes for Li–ion batteries, it was found that the post–treatment temperature of Bi–MOFs has a powerful impact on Li storage performance. Compared to Bi2 Se3 @NC–500 and Bi2 Se3 @NC–600 hybrids, Bi2 Se3 @NC–400 hybrids deliver large specific capacity, outstanding rate performance, and good cyclic stability. 410.6 mAh g −1 of capacity is gained after 50 cycles at 100 mA g −1 . Even at 500 mA g −1, 335.8 mAh g −1 is achieved after 400 cycles. The superior Li storage feature of Bi2 Se3 @NC–400 hybrids is ascribed to the synergetic effect between Bi2 Se3 nanosheets and N–doped nanocarbon. Bi2 Se3 @NC–400 hybrids is a promising anode material for LIBs.